Design of the car image system based on FPGA - Qiyan, Yan (2017 First International Conference on Electronics Instrumentation and Information Systems (EIIS), 2017)
The whole car image system based on FPGA select Spartan 3A-DSP (XC3SD1800A) produced by Xilinx as the core processor, the system will sample multi-video signal of CMOS within FPGA for video format conversion, Scaler processing, birdviews conversion, multi-video signal synthesis. This paper mainly introduces the hardware composition of the system and the system function frame. At the same time, a algorithm that the original video is formatted to Bayer format by RGB565 is delivered, this algorithm shows the realization method of template operation based on FPGA.